Design of a compact and effective greywater treatment system in Malaysia - Ong, Zhi Chao; Asadsangabifard, Mohammadjavad; Ismail, Zubaidah; Tam, Jun Hui; Roushenas, Peiman (Desalination Publications, 2019)
Water shortage has been one of the major concerns faced by about 2.7 billion people around the world due to several factors, including water pollution, climatic change, etc. Several nations have been seeking practical alternatives to address this issue and one of the most pragmatic approaches is the development and implementation of greywater treatment systems. To date, a great assortment of greywater treatment systems have been developed. The current study presents a different water treatment system to treat residential, commercial and industrial greywater in Malaysia. Unlike most existing systems which involve separate steps of treatment, the proposed method integrates aeration, disinfection and membrane filtration in a compact reactor, which could potentially reduce the operational cost, space and equipment. Aeration is required to promote pollutant degradation by aerobic microorganisms, while disinfection (UV) is needed to eliminate pathogenic bacteria. Subsequently, membrane filtration is used to remove suspended and dissolved pollutants of which are relatively smaller in size. The results have proven that the proposed system is effective in improving the quality of greywater, in which, the parameters (BOD, turbidity, total suspended solids, TDS, pH, DO) are reported to be in good agreement with the standards. While this study is conducted in a laboratory environment, its excellent results suggest that the proposed system is potentially practical for commercial use in future. © 2019 Desalination Publications. All rights reserved.